Local and Foreign Banks’ Advertising Appeals on Social Media: A Comparative Analytical Study - AL-Qudaimi, Hameed Radman (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to compare and contrast the advertisements of local, Arab, and foreign banks in terms of the advertising appeals used on some social media platforms (Instagram, X, YouTube). Methods: This study is descriptive, and it uses different methods such as content survey and comparative content analysis. (360) advertisements are analyzed using purposive sampling during the period between 1/1/2023 and 4/30/2023. Results: Comparing and contrasting local, Arab, and foreign bank advertisements in terms of the type of advertising appeals used reveals that both logical and emotional appeals rank first in the advertisements of foreign banks, local banks, and Arab banks, respectively. In terms of logical appeals, highlighting products’ features rank first in the advertisements of foreign banks, followed by local banks, then Arab banks. As for emotional appeals, highlighting comfort ranks first in the advertisements of foreign banks, followed by local banks, then Arab banks. The study also shows that there are statistically significant differences between the advertisements of local, Arab, and foreign banks in terms of advertising appeals, logical appeals, marketing objectives, and advertising language attributed to the bank identity variable (local, Arab, foreign). However, there are no statistcially significant differences in terms of emotional appeals or advertising characters. Conclusion: The study recommends using advertising appeals that suit local, Arab and foreign consumer culture in order to achieve the desired benefits from the promotion process. It also recommends paying attention to the advertising design for marketing.